Use of Denaturing HPLC to Map Human and Murine Genes and to Validate Single-Nucleotide Polymorphisms. (April 2000) - Schriml, Lynn M.; Peterson, Raymond J.; Gerrard, Bernard; Dean, Michael
Linkage mapping has been extensively applied in the murine and human genomes. It remains a powerful approach to mapping genes and identifying genetic variants. As genome efforts identify large numbers of single-nucleotide polymorphisms, it will be critical to validate these polymorphisms and confirm their gene assignment and chromosomal location. The presence of pseudogenes can confuse such efforts. We have used denaturing HPLC to identify polymorphisms in human genes and to genotype individuals in selected CEPH pedigrees. The same approach has been applied to the mapping of murine genes in interspecies backcross animals. This strategy is rapid, accurate and superior in several respects to other technologies.